Correlation between Vertical Dimension of Occlusion and Finger Length in Kashmiri Population - Nazir, Shazana; Zargar, Nazia Majeed; Khurshaid, Syed Zameer; Shah, Asim Farooq; Naz, Falak; Malik, Mohsin (Journal of Orofacial Research, 2015)
Introduction: Measurement of accurate vertical dimension of occlusion (VDO) is of prime importance to the dentist especially a prosthodontist. Though many methods have been proposed in recording VDO in the past but none of them fulfills the criteria of accuracy, reproducibility and ease. This study employs theuse of length of fingers to measure VDO in Kashmiri population. Materials and methods: The study was conducted on 60 dentulous subjects which include 30 males and 30 females in the age range of 18 to 25 years. Measurement of VDO and length of fingers was recorded using a digital vernier caliper. Correlation between VDO and length of fingers was studied using Spearman’s coefficient. Result: Vertical dimension of occlusion was found to be almost the length of index finger in males and little finger in females in Kashmiri population. Conclusion: The study revealed that length of index finger is almost equal to VDO in males and length of little finger is almost equal to VDO in females.